Impact of Surgical Timing on Outcomes in Neonatal Inguinal Hernia Repairs: A Systematic Review - Leen Yahya Alqahtany; Arwa Alsharif; Abdulaziz Alsharif; Omar Alanazi; Manaf Altaf; Ahlam Kaleemullah; Lana Alsaedi; Hanan Ismail Wasaya; Abrar Hassan Alharbi; Osama Bawazir (Pediatric Reports)
Inguinal hernia repair (IHR) is a common surgical procedure among neonates and infants; the time of surgery is one of the major factors affecting its outcomes. Our systematic review aims to evaluate the effects of surgical timing on outcomes in inguinal hernia repairs in the newborn and infant population to establish evidence-based guidelines for optimal surgical timing. A systematic search was performed in PubMed, MEDLINE, and Web of Science databases, following PRISMA guidelines. Studies evaluating neonates and infants undergoing IHR with outcomes of recurrence, complications, and postoperative recovery were included. Data were collaboratively extracted, including patient demographics, surgical approaches, perioperative complications, and long-term outcomes. Early repair (0–28 days of life) decreased the risk of hernia incarceration but also increased the risk of preoperative complications. Delayed repair (29 days to 1 year of life) showed fewer preoperative complications but increased the risk of incarceration. The outcomes were affected by variables including patient maturity and comorbidities, along with hernia severity. Neonates with a high risk for incarceration are best treated with early repair, while stable infants can be managed safely with delayed repair. More randomized trials are needed to develop standardized guidelines that balance the associated risks of neonatal versus infant repair strategies to maximize benefits.